Estudio del comportamiento del consumidor en la compra de productos de belleza en al ciudad de Machala - Alvarado Piña, Marlon Leonel (2015)
The present research focuses on evaluating the factors that influence behavior with women aged 15-55 years compared to buying beauty products in the city of Machala. It was necessary to build on previous research of authors who allowed one way or another thoroughly aware of the changes over time has been the consumer especially the importance of buying beauty products. When information was collected using observation instruments as guides allowing the author to continue their buying process and surveys where it was determined that machaleñas for both young and adult women, the use of beauty products especially makeup in their daily lives is of great importance. These consumers are riding the wave of trends that arrive every day, as well as seeking new stores that offer the market, purchase frequency is monthly, for they take two to four products through the influence of advertising and recommendations of friends who act in their purchasing decision, because feeling good about itself and improve the image of the face is what they seek. With these results it starts to design a marketing plan with internal, external and interactive strategies that allow Stores Mendieta's adapting to new consumer trends present mitigate the perception of current image people have of the store and in addition to that increase its market share.